Verification of Alternative Agar Plate Method for Quantitative Analysis of Yeasts and Molds in Cocoa Products - Chairia Faulita Ananti; Uswatun Hasanah; Harsi Dewantari Kusumaningrum (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Cocoa beans are vital raw materials in the food industry and are processed into various cocoa products. These products must meet quality and food safety standards, as contamination by yeasts and molds can reduce product quality and shelf life. Conventional microbiological methods often require long incubation times, delaying quality control. This study aimed to verify Symphony Agar as a rapid method for enumerating yeasts and molds in cocoa products following ISO 16140-3:2021 guidelines and to compare it with conventional methods. Verification consisted of two stages: (1) implementation verification, assessing standard deviation of intralaboratory reproducibility (SIR), and (2) food item verification, assessing estimated bias (eBias). Implementation verification on cocoa powder yielded SIR values of 0.121 log₁₀ CFU (pour plate) and 0.171 log₁₀ CFU (spread plat), both below the acceptable threshold, indicating good reproducibility. Food item verification using cocoa powder, cocoa cake, and cocoa liquor showed eBias values under 0.5 log₁₀, meeting the requirements. A comparative study using an independent t-test found no significant difference between Symphony Agar and DG18 Agar. The results indicate that Symphony Agar is suitable as an alternative medium for yeasts and molds analysis in cocoa products, offering the benefit of a shorter incubation time without compromising accuracy.